DRAFTING AGREEMENT FOR CHARTERING SHIP WORKS AT MODERN KENCANA PERKASA PT BATAM - Liand Maulidina; Winda Fitri (ConCEPt - Conference on Community Engagement Project, 2022)
Indonesia is a state of law. Because of the rule of law, all the actions of the people are regulated by laws and regulations. Referring to this matter, of course, it is clearly regulated regarding the rights and obligations of each legal subject. Both individuals and/or legal entities must always be on the lookout for situations in the future that can later harm themselves. Including the Company in carrying out its activities. As a preventive measure against the agreement as described above, the chartering service party is obliged to pay attention to a binding agreement that has legal force before carrying out a cooperation which according to the law of this country can be strong evidence if in the future things outside the agreement occur. Therefore, the author intends to assist companies in making agreements for the benefit of cooperation with partners.